Dynamic Hedging for Managing Financial Risk Exposure : An Empirical Study on Derivatives - Aydin, Elifnaz (2024)
Dynamic hedging can be strategically important and beneficial for managing financial risk exposure for a variety of businesses. This thesis aims to explore dynamic delta hedging of currency options on a hypothetical portfolio strategy in a simulation setting. The calculations are carried out using the Black-Scholes model. The dynamic delta hedging strategy is compared to static hedging and no delta hedging for the selected currency pair EUR/USD. The results suggest that dynamic delta hedging stands out by being both adaptable and predictable among the three strategies and is therefore considerable for entities prioritizing risk management over potential for high gains.